The development of Rab27-effector protein interaction inhibitors for treatment of cancer cell invasion and proliferation - Al-Saad, Raghdan Zeki Chillab (2017)
There are more than 60 Rab proteins in mammals constituting the largest family among the Ras superfamily of GTPases. Rab proteins are essential components of the intracellular secretory machinery, regulating transport and exocytosis of various intracellular organelles including secretory granules. Rab-regulated secretory functions are exerted by interaction with their downstream effector proteins, preferentially when they are activated into their GTP-bound state. Accordingly, Rab proteins can switch from active to inactive states through cycling from GTP- and GDP- bound forms, respectively. The Rab27 subfamily consists of Rab27a/b isoforms that have similar but not identical functions. Those functions include the regulation of trafficking, docking and fusion of various lysosome-related organelles and secretory granules; such as melanosomes in melanocytes and lytic granules in cytotoxic T lymphocytes. Rab27a/b exert their specific and versatile functions by interacting with eleven effector proteins, preferentially in their GTP-bound state. In recent years, a number of studies have identified roles for Rab27 proteins and their effectors in cancer cell invasion and metastasis, immune response, inflammation and allergic responses. These findings suggest that Rab27-effector protein interaction inhibitors could contribute to the development of effective strategies to treat these diseases. However, there has been very little research reported on the development and identification of such inhibitors. The foremost aim of the present study was to identify and develop candidate inhibitors of Rab27-effector protein interactions. To this end, fluorescent GST-pull down and FRET-based protein-protein interaction assays were developed to be used as in vitro read-outs for Rab27-effector interactions. In addition, a melanosome clustering assay was used as an indirect read-out for Rab27-effector protein interactions in living cells. The binding affinity of Slp1 and Slp2 effectors was determined using those in vitro assays. Furthermore, essential determinants of Rab27-Slp2 effector interaction were characterised and used to develop Slp2 super-effectors. The findings of this study suggest that the development of Rab27 super-effectors is an effective strategy to inhibit Rab27-effector interactions.